Balance between geographic, soil, and host tree parameters to shape soil microbiomes associated to clonal oak varies across soil zones along a European North–South transect. (24th February 2021) - Habiyaremye, Jean de Dieu; Herrmann, Sylvie; Reitz, Thomas; Buscot, François; Goldmann, Kezia
Summary: Tree root‐associated microbiomes are shaped by geographic, soil physico‐chemical, and host tree parameters. However, their respective impacts on microbiome variations in soils across larger spatial scales remain weakly studied. We out‐planted saplings of oak clone DF159 ( Quercus robur L.) as phytometer in four grassland field sites along a European North–South transect. After four years, we first compared the soil microbiomes of the tree root zone (RZ) and the tree root‐free zone (RFZ). Then, we separately considered the total microbiomes of both zones, besides the microbiome with significant affinity to the RZ and compared their variability along the transect. Variations within the microbiome of the tree RFZ were shaped by geographic and soil physico‐chemical changes, whereby bacteria responded more than fungi. Variations within both microbiomes of the tree RZ depended on the host tree and abiotic parameters. Based on perMANOVA and Mantel correlation tests, impacts of site specificities and geographic distance strongly decreased for the tree RZ affine microbiome. This pattern was more pronounced for fungi than bacteria. Shaping the microbiome of the soil zones in root proximity might be a mechanism mediating the acclimation of oaks to a wide range of environmental conditions across geographic regions.